PERBANDINGAN PENGATURAN PENGADAAN BARANG DAN JASA DI LINGKUP BUMN ANTARA NEGARA INDONESIA DAN MALAYSIA: Comparison Of Arrangement For The Procurement Goods And Services Within The Scope Of Soes Between Indonesia And Malaysia - Raizidane Zavier Rais; Rosdiana Saleh (AMICUS CURIAE, 2025)
Government procurement of goods and services plays an important role in encouraging economic growth for the welfare of the people. SOEs as strategic economic actors also support the national economy based on the principles of economic democracy. In procuring goods and services, SOEs have Standard Operating Procedures (SOP) in accordance with applicable laws and regulations. In Indonesia, procurement is regulated through the Regulation of the Minister of SOEs Number PER-2/MBU/03/2023 with a normative and bureaucratic approach that emphasizes procedural compliance. Malaysia through the Red Book: Procurement Guidelines & Best Practices adopts a strategic and flexible approach oriented towards Good Corporate Governance and value for money. This study identification problem about the similarities and differences in Standard Operating Procedures (SOPs) for the procurement of goods and services within the scope of Indonesian and Malaysian SOEs, as well as the obstacles in conducting legal comparisons. The method used is normative with a descriptive analytical legal comparative approach. The results and conclution of article show that while both uphold the principles of transparency and accountability, Malaysia's system more adaptive and innovative through digitalization. Indonesia still faces bureaucratic and institutional challenges. Legal comparative obstacles arise from differences in the basic legal system adopted by each country.